2000
DOI: 10.1128/jcm.38.11.3932-3936.2000
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between Clinically Relevant and Nonrelevant Acanthamoeba Strains Isolated from Contact Lens- Wearing Keratitis Patients in Austria

Abstract: Eighteen cases of Acanthamoeba-associated keratitis among contact lens wearers seen at the Department of Ophthalmology, Karl-Franzens-University, Graz, Austria, between 1996 and 1999 are reviewed. The amoebae were proven to be the causative agents in three patients. The aim of our study was to discriminate between clinically relevant and nonrelevant isolates and to assess the relatedness of the isolates to published strains. Altogether, 20 strains of free-living amoebae, including 15Acanthamoeba strains, 3 Vah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(34 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…; Walochnik et al. ). Although growth of Acanthamoeba at and over 37 °C is indicative of pathogenic potential, Schuster () proved that some clinical isolates grow better at 30 °C.…”
Section: Resultsmentioning
confidence: 99%
“…; Walochnik et al. ). Although growth of Acanthamoeba at and over 37 °C is indicative of pathogenic potential, Schuster () proved that some clinical isolates grow better at 30 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Acanthamoeba serves as a carrier for different microorganisms to humans, acting as a vehicle for the circulation of pathogens between the environment and humans (Krusnell and Linder, 2001;Huws et al 2008). Various Acanthamoeba species have been reported to be able to cause keratitis and other human infections, among which the most prevalent are A. castellani, A. polyphaga, A. rhysodes and A. hatchetti (Walochnik et al 2000a;Khan 2006). Although easily recognized at the genus level by their polygonal cysts, the accurate Acanthamoeba species determination and pathogenic potential involves molecular analysis (PCR, RFLP-PCR or DNA sequencing) and several behavioral tests (osmotolerance, temperature tolerance and cytotoxicity assays) which can require axenic and clonal amoeba cultures (Walochnik et al 2000b).…”
Section: Introductionmentioning
confidence: 99%
“…One genotype, designated T4, has been found in nearly all AK infections. Rarely, genotypes T3 [Ledee et al 1996) and T11 (Khan et al 2002), and in one case genotype T6 (Walochnik et al 2000a) have been observed in AK infections. Other infections caused by Acanthamoeba spp.…”
mentioning
confidence: 99%